2021
DOI: 10.1108/ijm-05-2020-0244
|View full text |Cite
|
Sign up to set email alerts
|

How GHRM is related to green creativity? A moderated mediation model of green transformational leadership and green perceived organizational support

Abstract: PurposeThis study aims to examine the relationship between green human resource management (GHRM) practices and green transformational leadership toward inducing employees' green creativity. Specifically, drawing upon the ability, motivation and opportunity theory, the authors tested how green perceived organizational support (green POS) mediates the link between GHRM practices and employees' green creativity. Furthermore, based on the firm's resource-based view, the authors examine the moderating role of gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 70 publications
4
75
0
3
Order By: Relevance
“…For example, Aboramadan et al (2021) found that climate for green creativity partly mediated the impact of environmentally specific servant leadership on hotel employees’ organizational citizenship behavior for the environment. Hameed et al ’s (2021) work indicated that perceived green organizational support fully mediated the effect of green human resource management on green creativity. Nisar et al (2021) also showed that green intellectual capital completely mediated the effect of green human resource management on hotel employees’ PEB.…”
Section: Literature Review and Hypothesesmentioning
confidence: 94%
“…For example, Aboramadan et al (2021) found that climate for green creativity partly mediated the impact of environmentally specific servant leadership on hotel employees’ organizational citizenship behavior for the environment. Hameed et al ’s (2021) work indicated that perceived green organizational support fully mediated the effect of green human resource management on green creativity. Nisar et al (2021) also showed that green intellectual capital completely mediated the effect of green human resource management on hotel employees’ PEB.…”
Section: Literature Review and Hypothesesmentioning
confidence: 94%
“…The mediating role of POS in influencing different employees' outcomes was mentioned by prior researchers [31,32]. Even from an environmental perspective, the debate on green POS (GPOS) also exists [33,34]. Nevertheless, the important mediating role of GPOS in a leadership framework to spur the EPEB of employees was previously ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Green HRM refers to practices that pursue to decrease the ecological and environmental influence of businesses and it is related to the firm's environmental strategy and its employees' green behavior (Al‐Swidi et al, 2021). Green HRM is a critical component of literature on sustainable human resource management, as it serves as a bridge to integrating HRM practices with activities for the corporation's environmental management and sustainable resource development (Hameed et al, 2021; He et al, 2021). As such, green HRM practices involve the integration of a firm's ecological management objectives into its HRM practices, specifically in hiring, training and engagement, performance management, and compensation (Guerci et al, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%